Kiai Hasan Ulama Mursyid Tarekat Shaththariah As a Pioneer of Modern Pesantren - Rahmat, Munawar (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
Pesantren is a native Islamic education institution of Indonesia; while the school is a modern educational institution. The tested pesantren excelled in the development of religiosity, simple lifestyle, and independence of the santri; while schools excel in the intellectual and vocational development of the students. Learning in pesantren uses an individual system, while the school uses a classical system. Kiai Hasan Ulama is the Mursyid of the Tarekat Shaththariah, better known as Wasithah, precisely Wasithah 43 (1873-1916). In 1886, he founded Pesantren Takeran (Magetan East Java) as the first modern pesantren in Indonesia that combines the excellence of pesantren and school systems. The educational model is preserved by Wasithah to the present, namely Pesantren Sabilul Muttaqien (PSM) Takeran (Wasithah 44-45), PSM Tanjunganom Nganjuk (Wasithah 46), Pondok Modern Resources At-Taqwa (Pomosda) Tanjunganom Nganjuk (Wasithah 47), and Pondok Pesantren Matlabus Salik (Pondok Al-Matlab) Jogomerto Nganjuk (Wasithah 48/now). The study aims to describe the modern pesantren model established by Kiai Hasan Ulama. The study method used a qualitative approach with documentary study techniques ((on main ideas of Mursyid), ex post facto (educational institution of Wasithah 47), and depth interview with the Wasithah now. The study found that Pesantren Pomosda (2008-2012) and Pesantren Al-Matlab (2016 -...) is the present Pesantren Takeran that runs the school system excellence in pesantren ways.